(untitled) (Journal of Social Sciences Review, 2022)
Post-COVID-19 outbreaks and the Russian-Ukraine war seriously disturb the energy supply chain, which causes massive inflation worldwide. This inflation badly affected developing countries because of the poor population living in these countries. This study explores the different determinants of inflation in Pakistan by considering the global crude oil prices (COP) energy prices by using the annual time series data from 1980 to 2020. This study measured inflation by using CPI as the dependent variable, while COP was the key independent variable by controlling the exchange rate, GDP, and remittances. The empirical results are estimated by using the non-linear ARDL econometric approach. The study proposes the U-shaped relationship of COP with CPI. Furthermore, foreign remittance and GDP per capita also contribute to domestic inflation. The present study suggests that government should take steps to decrease dependence on imported energy resources to make Pakistan prosperous.